Resilience-related Breast Cancer: A Concept Analysis - Fitria Endah Janitra; Nur Aini; Anggi Lukman Wicaksana (Department of Nursing, Faculty of Medicine, Diponegoro University, 2023)
Background: Breast cancer-related adversity can result in severe psychological issues. However, some patients were able to demonstrate resilience, while others were not. Therefore, the concept of resilience in breast cancer patients requires further clarification.Purpose: This study aimed to systematically analyze resilience in patients with breast cancer, its attributes, antecedents, consequences, and empirical referents.Methods: This concept analysis used the Walker and Avant method. CINAHL, Embase, Scopus, Web of Science, PubMed, Cochrane, and Medline-OVID databases were explored using the keywords ‘resilience*’ and ‘breast cancer’. Papers discussing resilience among breast cancer patients were used as criteria for inclusion. The analysis focused on the redefinition of resilience-related breast cancer by identifying attributes, antecedents, and consequences.Results: A total of 53 studies were analyzed to construct resilience among breast cancer patients. The analysis identified that resilience in breast cancer patients has three defining attributes: coping, optimism, and social support. The antecedents were body image after mastectomy, symptom distress, cancer-related stigma, and fear of cancer recurrence, while the consequences included recorded as the quality of life and post-traumatic growth.Conclusion: Critical characteristics of resilience in breast cancer patients were coping, optimism, and social support. Thus, improving those characteristics might improve the quality of life and post-traumatic growth.